Neonatal seizures: our experience of incidence, etiology and outcome in a tertiary care centre - Anand, Veena; Pillai, Swapna K; Jayakrishnan, Deepa; Nair, PMC (Indian Journal of Child Health, 2014)
Context: Neonatal seizures often evoke a sense of urgency among physician in charge of newborn as they often indicate a CNS dysfunction. Incidence of neonatal seizures remains high in our community even in this era of advanced perinatal care. Early detection of seizure and its etiology help us to provide specific therapy.Objectives: The purpose of this study was to determine the incidence, etiology and outcome of neonatalseizures. Settings and design: Prospective hospital based descriptive study conducted in the neonatal unit oftertiary care hospital. Material and methods: Consecutive newborns admitted with seizures were included inthis study. Data were collected regarding relevant history and examination, thoroughly evaluated for etiologyand outcome was documented. Analysed by descriptive statistics and conclusions were drawn. Results: Onehundred and eight newborns with seizures were included during study period and incidence of neonatal seizure was 5.5%. Hypoxic ischemic encephalopathy (HIE) and sepsis constituted the most common etiologies. HIE was the most common etiology associated with mortality. Abnormal EEG with supressed background activity was present in majority of mortality cases. Conclusion: Most of the cases had multifactorial etiology. Measures for prevention, prompt recognition and specific management of neonatal seizure help to reduce the burden of neonatal morbidity in the community.